Lived Experiences of Parents of Gifted Students With Autism Spectrum Disorder: The Struggle to Find Appropriate Educational Experiences. (October 2015) - Rubenstein, Lisa DaVia; Schelling, Natalie; Wilczynski, Susan M.; Hooks, Elizabeth N.
The purpose of this phenomenological, qualitative study was to illuminate the lived, shared experiences of parents of gifted children diagnosed with autism spectrum disorder. Thirteen parents were interviewed and the interviews were transcribed and qualitatively analyzed. This article specifically examines the parents' experiences navigating the educational system for their children. All participants described the challenges associated with finding appropriate educational placements for their children due to the children's unique social and academic needs. Parents recognized the incompatibility between their child's characteristics and typical educational environments, and this incompatibility required parents to take an active role in designing and finding appropriate educational opportunities. These findings provide insight for school personnel and parents as they develop flexible services for twice-exceptional students.